ANALYSIS AND MODELLING OF COMPLEX DECISION SITUATIONS - Rasou, Najah (University of Thi-Qar Journal of Science, 2019)
This paper suggests specific logical ideas that lead to scientific analysis and building implementable models for complex decision situations that arise in modern organizations. These models should be easilunderstood and applied by decision makers in a changed system environment with multiple objectives.